PENGGUNAAN WIKIPEDIA SEBAGAI MEDIA PEMBELAJARAN DARING FIKIH MATERI PUASA RAMADHAN MI AL-IKHLASH SURABAYA - Weni Marina; W N Istiqomah; Mokhamad Syaifudin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Online learning is the preparation of learning that is implemented at home. An online learning policy has been set by the education minister to reduce the spread of Covid-19. MI Al-Ikhlash Surabaya carried out learning based on the policy during the pandemic through information technology. Learning that is applied from lower to upper grades could not be separated from web-based internet and mobile learning media. With the internet-based learning media, all students of MI AlIkhlash Surabaya could adapt and participate in online learning. During the learning of Pondok Ramadhan, one of the religious teacher’s actions to provide material for Ramadan fasting is to use Wikipedia. Thus, the researchers discussed how the successful implementation of Wikipedia in the Islamic boarding school at MI Al-Ikhlash Surabaya during online learning while Ramadan. Type of the study applied in this article was a qualitative type. Data collection techniques used were observation, interviews, and documentation. The data results obtained were from Wikipedia, which could be used as a learning resource during online learning. It could be applied in the form of a summary of the Wikipedia source that was potentially free. The advantage of Wikipedia in this study was seen from the use of reading material and forms the character of students' literacy. While the disadvantages of Wikipedia in this study were the lack of students’ interest in reading and the network problem of students’ less attractive because the teacher united it remotely.